Soil Water Status On Some Type Of Soil On Coffee Farm Of Central Aceh - khairun Purgawa; Darusman Darusman; Syamaun A. Ali (Jurnal Ilmiah Mahasiswa Pertanian, 2016)
Abstract The district of Central Aceh is one of district located in the highlands of Gayo. The land and environtmant are very promising which is really potential to development of farming sector primarily coffee plant. Information on moisture groundwater is necessary to improve the potential ground for the coffee plant. Coffee plants are already known suitable developed in the district of Central Aceh. But, information on the status of groundwater in certain kind of soil unavailable, although the availability of water can be done with the irrigation. The results showed that among 3 types of studied soils are that andisol, ultisol and inceptisol and the highest water available is ultisol dominated by a non cultivation. Even andisol having value the availability of water is more stable, this can be seen from the water available that is not very different between land cultivation and non cultivation. While other land types that Ultisol and Inceptisol only have water available on of non cultivation only. If it is associated with the availability of water in the coffee plant is then the Andisol is most suitable because soil water on the two different locations aren’t different .